2014
DOI: 10.3928/01477447-20140728-91
|View full text |Cite
|
Sign up to set email alerts
|

Markedly Elevated Intra-articular White Cell Count Caused by Gout Alone

Abstract: Joint pain accompanied by erythema, swelling, and decreased range of motion is concerning for septic arthritis and typically warrants joint aspiration. The synovial fluid white blood cell count plays a central role in the decision-making process regarding these patients. Traditional teaching holds that a cell count greater than 50,000 white blood cells/µL is likely caused by infection and therefore warrants either operative intervention or serial aspiration. This report describes 2 patients with extremely high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Crystal-induced arthritis may present with clinical manifestations that are identical to those of a PJI [72], and high WBC counts are reported in cases of acute gout (e.g. ; up to 500,000 cells/µL) [73]. It should be noted that the presence of crystal arthritis does not rule out a concurrent PJI.…”
Section: Co-morbid Conditionsmentioning
confidence: 99%
“…Crystal-induced arthritis may present with clinical manifestations that are identical to those of a PJI [72], and high WBC counts are reported in cases of acute gout (e.g. ; up to 500,000 cells/µL) [73]. It should be noted that the presence of crystal arthritis does not rule out a concurrent PJI.…”
Section: Co-morbid Conditionsmentioning
confidence: 99%
“…Although we are not aware of any published laboratory values that are used as a threshold for the diagnosis of septic ankle arthritis, a synovial WBC count of .50,000 cells/mm 3 is the standard cutoff that is used for native joints throughout the body 5,31,[36][37][38][39] . Nevertheless, this value has been debated, and previous research has shown that using 50,000 cells/mm 3 as a threshold for infection has a sensitivity of only 64% 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Although secondary to detecting pathogen presence, measuring leukocyte levels are useful in the diagnosis of PJI. Similar to other secondary methods, however, leukocyte levels are not specific for PJI and can be increased because of other causes of inflammation such as gout [70].…”
Section: Leukocytesmentioning
confidence: 99%